Teak Plantations in the Andamans - Subramaniam, B. A. (Indian Forester, 1956)
The history of Teak plantations in the Andamans has been traced since their beginning in 1883 and information regarding the methods adopted in raising the plantations, their present condition, etc., has been compiled, from the old Working Plans for Andaman Forests. Detailed investigations were carried out by the writer on the Long Island Plantation of 1927 and by Working Plan Staff on the Goplakabang Plantation of 1889. The measurements indicate that teak grows well in the Andamans, and should prosper if plantations are looked after well from the start. Recently Teak plantations have again been started on an experimental scale in South and North Andaman Divisions. Seed for these was obtained from Nilambur and the well established method of pre-monsoon stump-planting has been adopted. This note, it is hoped, will serve to guide future work on teak as well as to maintain the continuity of the history of teak in the Andamans.